(untitled) (AYUSHDHARA, 2024)
Psoriasis is a chronic inflammatory, hyperproliferative skin disease. It is characterised by well-defined, erythematous scaly plaques, particularly affecting extensor surfaces, scalp and nails, and usually follows a relapsing and remitting course. Psoriasis affects approximately 1.5%-3% of populations of European ancestry but is less common in Asian, South American and African populations. It occurs equally in both sexes and at any age; although it is uncommon under the age of 5 years, more than 50% of patients present before the age of 30 years. Aims and Objectives: To find out the effect of Ayurvedic medicine and Shodhan chikitsa in the management of Mandal kushtha (psoriasis). Material and Methods: A 53-year-old male patient having complaint of skin lesion on scalp, upper back and abdomen area with red demarcation from last 15 years. Lesion having silvery scales and falling all rubbing with severe itching. This condition clinically correlated to Mandal Kushtha described in Ayurveda. Mandal Kushiha has Shwelam Raklam varna, Sthirar, Styanam and Utsana Mandala (skin begins with special characters. Acharya Charaka mentioned Shodhan Chikitsa for purification of Kushtha Roga. Result and Discussion: Considering The sign and symptoms patient was treated with classical Vamana Karam (therapeutic emesis) and Virechana karma (therapeutic purgation) according in line of treatment of Kushtha (psoriasis). Assessment was done before treatment, after treatment and after follow-up. Pictures were taken before treatment and after treatment. Remarkable improvement was noticed in scaling, induration and itching after Vamana and Virechanа treatment and residue only hyper pigmented pink lesion.